Nanoclays and mineral derivates applied to pesticide water remediation - Lousada, María E. [UNESP]; Lopez Maldonado, Eduardo A.; Nthunya, Lebea N.; Mosai, Alseno; Antunes, María Lucia Pereira [UNESP]; Fraceto, Leonardo F. [UNESP]; Baigorria, Estefanía [UNESP] (Elsevier, 2023)
Although pesticides are vital in agroecosystems to control pests, their indiscriminate use generates innumerable environmental problems daily. Groundwater and surface water networks are the most affected environmental matrices. Since these water basins are mainly used to obtain water for human consumption, it is a challenge to find solutions to pesticide contamination. For these reasons, development of efficient and sustainable remedial technologies is key. Based on their unique properties including high surface area, recyclability, environmental friendliness, tunable surface chemistry and low cost, nanoclays and derived minerals emerged as effective adsorbents towards environmental remediation of pesticides. This study provides a comprehensive review of the use of nanoclays and mineral derivatives as adsorbents for pesticides in water. For this purpose, the characteristics of existing pesticides and general aspects of the relevant clays and minerals are discussed. Furthermore, the study provides insightful discussion on the potential application of nanoclays and their derivatives toward the mitigation of pesticide pollution in the environment. Finally, the outlook and future prospects on nanoclay implications and their environmental implementation are elucidated.
Keywords: Agrochemicals; Environmental remediation; Nanomaterials; Sustainable adsorbents